2012
DOI: 10.1590/s1676-26492012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Pre-surgical mood disorders associated to worse post-surgical seizure outcome in patients with refractory temporal lobe epilepsy and mesial temporal sclerosis

Abstract: SUMMARYObjectives: This study aims at verifying the impact of pre-surgical PD on seizure outcome in patients with refractory temporal lobe epilepsy and mesial temporal sclerosis (TLE-MTS). Methods: After previous consent, retrospective data from 115 surgically treated (corticoamygdalohyppocampectomy) TLE-MTS patients (65 females; 56.5%) were analyzed. Psychiatric evaluations were performed through DSM-IV criteria. Engel IA was established as a favorable prognosis. Results: Forty-five patients (41.6%) were clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…In a large cohort of subjects with newly diagnosed epilepsy, a history of psychiatric comorbidity was associated with progression to refractory disease [42]. De Araújo Filhoa et al [65] found a statistically significant association between the absence of pre-surgical psychiatric disorder and a favorable seizure outcome which was reported by other researchers [18,46,66]. Thus it is essential to have a pre and post surgical psychiatric assessment of patients.…”
Section: Presurgical and Postsurgical Psychiatric Assessmentmentioning
confidence: 82%
“…In a large cohort of subjects with newly diagnosed epilepsy, a history of psychiatric comorbidity was associated with progression to refractory disease [42]. De Araújo Filhoa et al [65] found a statistically significant association between the absence of pre-surgical psychiatric disorder and a favorable seizure outcome which was reported by other researchers [18,46,66]. Thus it is essential to have a pre and post surgical psychiatric assessment of patients.…”
Section: Presurgical and Postsurgical Psychiatric Assessmentmentioning
confidence: 82%
“…A interação entre epilepsia e depressão / ansiedade tem um impacto negativo sobre o controle de crises epilépticas após o tratamento cirúrgico. Um estudo brasileiro avaliou 115 pacientes com epilepsia de lobo temporal submetidos à amigdalohipocampectomia e demonstrou que o TDM pré-cirúrgico foi o mais significante preditor relacionado ao desfecho desfavorável de controle de crises 46 . Tais achados reforçam a existência de uma interação entre processos neurobiológicos deletérios comuns à presença de sintomas psiquiátricos (como os depressivos e de ansiedade) e à geração de crises epilépticas 28 .…”
Section: Complicações Da Associação Entre Epilepsia E Depressão / Ans...unclassified